2012
DOI: 10.1016/j.ygeno.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of physiological traits associated with salt tolerance in Medicago truncatula Recombinant Inbred Lines

Abstract: In this study, QTL mapping of physiological traits in the model Legume (Medicago truncatula) was performed using a set of RILs derived from LR5. Twelve parameters associated with Na+ and K+ content in leaves, stems and roots were measured. Broad-sense heritability of these traits was ranged from 0.15 to 0.83 in control and from 0.14 to 0.61 in salt stress. Variation among RILs was dependent on line, treatment and line by treatment effect. We mapped 6 QTLs in control, 2 in salt stress and 5 for sensitivity inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…A significant effect of genotype was observed for all traits. It is usually observed that shoot biomass traits have larger broad-sense heritability that root biomass traits (Arraouadi et al , 2012; Bouteillé et al , 2012), and the results obtained with the pouch-and-wick system confirm these observations (Table 3). Broad-sense heritability of root length typically ranges from 0.15 to 0.80 (Gahoonia and Nielsen, 2004; Bouteillé et al , 2012).…”
Section: Discussionsupporting
confidence: 61%
“…A significant effect of genotype was observed for all traits. It is usually observed that shoot biomass traits have larger broad-sense heritability that root biomass traits (Arraouadi et al , 2012; Bouteillé et al , 2012), and the results obtained with the pouch-and-wick system confirm these observations (Table 3). Broad-sense heritability of root length typically ranges from 0.15 to 0.80 (Gahoonia and Nielsen, 2004; Bouteillé et al , 2012).…”
Section: Discussionsupporting
confidence: 61%
“…Among them, the B3-DPB gene was consistently identified for all the traits analyzed in present analysis and germination under salt stress in the previous study. Comparable result was also obtained in M. truncatula (Arraouadi et al, 2012) where most of loci associated with salt related traits were located on chromosome 1. However, markers identified on chromosomes 5 and 6 in M. sativa by the present study were not reported in M. truncatula (Arraouadi et al, 2011, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…Numerous reports have been made on plant responses to salt stress and genes involved in salt tolerance have been identified and characterized in this species (See Rose, 2008 for review). QTLs for salt tolerance have been identified on chromosomes 1 and 8 in M. truncatula using recombinant inbred lines derived from a cross between the tolerant and susceptible parents (Arraouadi et al, 2011, 2012). However, limit report has been made on the genetics of the cultivated alfalfa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By now, salinity has become a main abiotic stress limiting crop production worldwide, affecting nearly 40 percent of agricultural lands located in arid and semi-arid areas (Mittler 2006; Roy et al 2014). Although many signaling components and molecular mechanisms have been identified which largely extend our understanding of plant tolerance against salt stress, the utilization of the knowledge in crop improvement leaves much to be desired since salt stress induces the genetic and physiological changes at all levels of organization in plants and the salinity tolerance, in common with other environmental stresses, relies on the interactions among multiple genes (Arraouadi et al 2012; Cortina and Culiáñez-Macià 2005; Flowers and Colmer 2015). Simply expressing one or several genes usually has no obvious improvement on the salt tolerance of transgenic crops.…”
Section: Introductionmentioning
confidence: 99%